Hubungan perilaku perawat dalam menerapkan edukasi pasien rawat inap di RSU Delia Kabupaten Langkat tahun 2022 - Andini Mentari Tarigan; Dyna Safitri Rakhelmi Rangkuti (Journal of Pharmaceutical and Sciences, 2023)
Health education is an educational activity carried out with the aim of changing a person's behavior from unhealthy to healthy behavior. Based on the initial survey conducted through interviews and observations (observations) in the inpatient unit of 10 nurses, it was found that 7 nurses did not provide a complete education, 3 other nurses had provided education but attitudes towards patients tended to pay less attention. The purpose of this study was to determine the relationship between nurse behavior in implementing inpatient education at Delia General Hospital, Langkat Regency. This type of research is quantitative by using an analytic survey method with a cross-sectional approach. The population in this study were all nurses totaling 60 people, and the samples taken using the total sampling technique were 60 people. Data analysis used univariate and bivariate analysis with the chi-square test statistic. The results of the chi-square test analysis showed that the p-value of knowledge variable obtained p-value = 0.000, attitude p-value = 0.000, and action p-value = 0.000 towards implementing inpatient education at Delia General Hospital, Langkat Regency. This study concludes that there is a relationship between knowledge, attitudes and actions towards implementing inpatient education at Delia General Hospital, Langkat Regency. RSU Delia Langkat Regency is recommended to carry out planning, assess the educational needs of patients, and evaluate the effectiveness of the education conducted. In providing education to patients and families, a well-planned preparation is necessary so that healthcare personnel have a clear understanding of how to prepare the appropriate equipment and resources to meet the actual needs of patients.